Taxonomic mystery solved: the identity of Melolontha pexa Zubkov, 1833 and the genus Adoretops Kraatz, 1883 (Coleoptera: Scarabaeidae: Melolonthinae) - Bezděk, Aleš; Bezděk, Jan; Shokhin, Igor V. (Zootaxa, 2026)
The identity of Melolontha pexa Zubkov, 1833 (Coleoptera: Scarabaeidae: Melolonthinae: Rhizotrogini) is clarified by the designation of a neotype. Melolontha pexa is transferred to the genus Holochelus Reitter, 1889 as Holochelus (Eriotrogus) pexus (Zubkov, 1833), new combination and proposed a senior subjective synonym of H. (Eriotrogus) aschhabadensis (Nonveiller, 1965) and H. (Holochelus) heptapotamicus Nikolajev, 2009. Although M. pexa Zubkov, 1833 is a primary junior homonym of Melolontha pexa Germar, 1823, its validity must be preserved according to the Article 23.9.5 of the International Code of Zoological Nomenclature (1999) and the case must be brought to the commission for a ruling. The type species of the genus Adoretops Kraatz, 1883 is designated as Demodema bonariensis Bruch, 1909, which was misidentified as Melolontha pexa Zubkov, 1833 in the original designation. This results in Adoretops becoming a new subjective junior synonym of Plectris LePeletier & Audinet-Serville, 1828 (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini). The history of the beetle material collected by G.S. Karelin between 1827 and 1836 in the vicinity of the Caspian Sea is summarized and the collaboration of Karelin and Zubkov is discussed.